Cultural rhetoric and metaphorical engine: The metaphor of stone in the social poetry of Gabriel Aresti - Luarsabishvili, Vladimer (Círculo de Lingüística Aplicada a la Comunicación, 2022)
Our article is an attempt to study the peculiarities of cultural rhetoric as the classical science of discourse that connects, on the one hand, rhetoric with culture and, on the other, culture with rhetoric. Rhetorical discourse makes cultural peculiarities explicit by using different figures of language, including metaphor; We analyze the role of the activation of metaphorical engine in the process of understanding the metaphor of stone in the poetic discourse of the Basque poet Gabriel Aresti.